Incorporação de inovações de origem externa considerando a complexidade tecnológica - Silva, Marco Antonio Costa da (2015)
Companies using open innovation find significant barriers in managing externally acquired technologies incorporation process, which is a critical challenge in evaluating technology investments. The central objective of this research was to construct and validate an incorporation model of technological innovation from external sources based on the assumptions of open innovation. The models that address open innovation processes in the literature are vague and imprecise in relation to the incorporation process and do not address important issues related to culture for innovation, absorption, and dynamic technological capabilities that are important theoretical foundations for innovation and contribute decisively to the incorporation process. The methods used in exploratory research proposed were quantitative. Data were collected by applying a structured questionnaire to managers of 1750 technology-based companies from various sectors of the economy, with a sample of 111 responses. Data analysis was performed using the software SmartPLS, by applying structural equation modeling with partial least squares and the template paths. It was found that the proposed initial model was validated almost entirely with minor adjustments. It could be concluded that the development of a culture for innovation, coupled with the construction of mechanisms for prospecting and processing of external sources of innovation, technological capability accumulation, and the ability to reconfigure internal resources, are important foundations to increase business efficiency in incorporating innovations/external technologies.